Prefererensi Nasabah Terhadap Produk Tabungan: (Studi pada Nasabah iB Muamalat di PT Bank Muamalat Indonesia Tbk) - Siska Yuli Anita (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2024)
The purpose of this article is to determine the partial and simultaneous influence of religiosity and service quality on customer preferences. This type of research is quantitative research with a research population of 273 people and a sample size of 73 respondents with sampling using the Slovin formula and sample selection criteria, namely that they are iB Hajj and Umrah savings customers of Bank Muamalat, aged 25-60 years and domiciled in Jakarta and Lampung. By using a data processing tool in the form of the SPPS version 20 application. The results of the research that has been carried out show that simultaneously religiosity and service quality have an influence on preferences, while partially religiosity has no effect on preferences and service quality has an influence on preferences. Keywords : Religiosity, Service Quality and Preference